Vāymoḻi vāypāṭṭuk kōṭpāṭṭu nōkkil Caṅka ilakkiyam - Tamiḻavaṉ (Cemmoḻit Tamiḻāyvu Mattiya Niṟuvaṉam, 2021)
Study on Sangam literature from Oral Formulaic Theoretical perspective
Literaturverzeichnis: Seite 133-134 und Index
Keywords: Sangam literature; Tamil poetry